Influence of sowing dates and zinc levels on yield and yield components of wheat (Triticum aestivum) - MOSHATATI, ALI; MOUSAVI, SAYED HASHEM (The Indian Journal of Agricultural Sciences, 2019)
In order to evaluate the influence of sowing dates and zinc levels on yield and yield components of wheat (Triticumaestivum L.) in Ahwaz, a split-plot experiment including three sowing dates (29 Nov, 14 and 30 Dec) in main plots and five zinc levels (0 (control), 10, 20, 30 and 40 kg/ha) in sub plots were implemented with three replicates in research farm of Agricultural Sciences and Natural Resources University of Khuzestan, Ahwaz, Iran. The mean comparison of sowing dates showed that the maximum grain yield was related to sowing date of 29 Nov and the minimum was obtained from 30 Dec. The mean comparison of zinc levels showed that the highest grain yield was in 30 kg/ha zinc and the lowest was in 0 kg/ha zinc. The mean comparison of interaction effect showed that the maximum grain yield was produced from 29 Nov and 30 kg/ha zinc and the minimum amount was related to 30 Dec and 0 kg/ha zinc. In general, in all sowing dates, zinc application increased grain yield of wheat.